2018
DOI: 10.21608/ejnf.2018.75603
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Brown Algae Supplementation in Drinking Water on Growth Performance and Intestine Histological Changes of Broiler Chicks

Abstract: imited research suggests the effect of brown seaweed in animal nutrition for improving gut health and performance, but there isn't any research suggests the effect of oral liquid seaweeds brown algae in broiler nutrition. So, this study was aimed to evaluate the effect of liquid brown seaweed algae (Ascophyllum nodosum) supplementation on broiler chick's performance and their intestine histology. The experimental chicks (total number of 120, one-day old, Indian River chicks) were used and fed the same diets du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Zahid et al (2001) showed that broiler chickens (Hubbard) fed on the normal feed containing brown seaweeds (10%, 20%, 30% and 40%) had higher body weight and a lower amount of fat while higher of protein as compared to controls [83]. Similar results were reported also for brown seaweed-Ascophyllum nodosum-which was added as a liquid to drinking water (1 mL/L) of Indian River chicks and significantly increased dressing color, breast width and length and decreased body fat when compared to the control chicks [53]. Much work has been dedicated to other brown seaweed-Sargassum sp.…”
Section: Carcass Characteristics and Meat Qualitysupporting
confidence: 62%
See 3 more Smart Citations
“…Zahid et al (2001) showed that broiler chickens (Hubbard) fed on the normal feed containing brown seaweeds (10%, 20%, 30% and 40%) had higher body weight and a lower amount of fat while higher of protein as compared to controls [83]. Similar results were reported also for brown seaweed-Ascophyllum nodosum-which was added as a liquid to drinking water (1 mL/L) of Indian River chicks and significantly increased dressing color, breast width and length and decreased body fat when compared to the control chicks [53]. Much work has been dedicated to other brown seaweed-Sargassum sp.…”
Section: Carcass Characteristics and Meat Qualitysupporting
confidence: 62%
“…Seaweeds can also be used in poultry nutrition in the liquid form (as extracts) or as extracted compounds and post-extraction residues. Abou El-naga and Megahed (2018) [53] examined the effect of brown seaweed (Ascophyllum nodosum) liquid in drinking water (1 mL/L) on broiler chickens' performance and their intestine histology, while Li et al (2018) tested ulvan extracted from green seaweed (Ulva sp.) as a feed additive for laying hens used at doses of 0.05%, 0.1%, 0.5%, 0.8% and 1% [47].…”
Section: Forms Of Seaweeds In Poultry Feedmentioning
confidence: 99%
See 2 more Smart Citations